Friday
March 24, 2017

Post a New Question

Posted by on .

hi I need help on this proof

ok I'm tyring to prove that

v^2 = v^20 + 2a(x -x0)

where the zeros are subscripts

ok the first step my book says is

start out with

x = x0 + average velocity (t)

then plug in average velocity

x = x0 + (2^-1(v + v0))t

ok and the next line it says

solve for t

and the next formula it shows

is
t = a^-1(v - v0)

ok how did you go from that line to this one?

Please show me

what happened to the two?
were did the a come from

I don' get it

Thanks!

  • AP Physics - ,

    I do not blame you but I will try.
    V^2 = Vo^2 + 2 a (X-Xo)
    is where you want to go
    ok
    X = Xo + (V+Vo)t/2
    V+Vo = 2 (X-Xo)/t

    Now what you seem to be missing is
    V = Vo + a t
    which you are supposed to know, the definition of constant acceleration (change in velocity = acceleration times time)
    so
    t =(V-Vo)/a

    then
    (V+Vo) = 2(X-Xo) a /(V-Vo)
    so then
    V^2-Vo^2 = 2 (X-Xo) a

  • AP Physics - ,

    This is a really, really, klutzy way to do this !!!

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question